Impact of comorbidities on perioperative outcomes for carcinoma of oral cavity - Katna, R (Ann R Coll Surg Engl, 2020)
INTRODUCTION: Surgical management of oral cavity carcinoma involves composite resection with reconstruction. Comorbidities increase the risk of perioperative complications. Objective stratification is important for uneventful recovery. The Charlson Comorbidity Index and the Washington University Head and Neck Comorbidity Index were used to assess perioperative morbidity and mortality. MATERIALS AND METHODS: This was a prospective study of 531 patients with head and neck squamous cell carcinoma who were treated between January 2014 and December 2017. Patients’ comorbidity scores on the Charlson Comorbidity Index and Washington University Head and Neck Comorbidity Index were recorded. RESULTS: The median age of the cohort was 49 years. Median Charlson Comorbidity Index score was 3 and Washington University Head and Neck Comorbidity Index was 0. There were five mortalities with a Charlson Comorbidity Index score of 4 or more. Fifteen patients had either infection, leak or postoperative bleeding. A Charlson Comorbidity Index of 4 or more was associated with higher event rate and poor overall survival (p=0.001) CONCLUSION: Higher Charlson Comorbidity Index score is associated with increased incidence of peri-operative morbidity and mortality, while the Washington University Head and Neck Comorbidity Index is a poor predictor of the same.